2016
DOI: 10.3847/0004-637x/819/2/91
|View full text |Cite
|
Sign up to set email alerts
|

THE SPATIALLY RESOLVED NUV–r COLOR OF LOCAL STAR-FORMING GALAXIES AND CLUES FOR QUENCHING

Abstract: Using a sample of ∼6000 local face-on star-forming galaxies (SFGs) we examine the correlations between the NUV-r colors both inside and outside the half-light radius, stellar mass M * , and Sérsic index n to understand how the quenching of star formation is linked to galaxy structure. For these less dust-attenuated galaxies, NUV-r is found to be linearly correlated with D 4000 n , supporting NUV-r as a good photometric indicator of stellar age (or specific star formation rate). First, we find that at M M 10 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 101 publications
4
15
0
Order By: Relevance
“…In NUV−u, the median of the colour difference is 0.23 mag; in u−i, the median of the colour difference is 0.19 mag. This negative colour offset is consistent with previous work (Pan et al 2014(Pan et al , 2016 where the authors found similar negative gradient in the NUV−optical colours in local galaxies. Nevertheless, there is a small fraction of galaxies having blue star-forming outer part but red quiescent inner part.…”
Section: Colour Distributionsupporting
confidence: 93%
“…In NUV−u, the median of the colour difference is 0.23 mag; in u−i, the median of the colour difference is 0.19 mag. This negative colour offset is consistent with previous work (Pan et al 2014(Pan et al , 2016 where the authors found similar negative gradient in the NUV−optical colours in local galaxies. Nevertheless, there is a small fraction of galaxies having blue star-forming outer part but red quiescent inner part.…”
Section: Colour Distributionsupporting
confidence: 93%
“…Histories of stellar mass assembly for galaxies are mainly classified into two distinct modes: "inside-out" and "outsidein" (Pan et al 2016;). In the "inside-out" assembly mode, star formation quenching takes place first in the center region of a galaxy, which may be due to AGN feedback depleting, heating or blowing out the gas in galactic center (e.g., Kauffmann et al 2004, Croton et al 2006, Fabian 2012, Dekel & Burkert 2014 or the bulge stabilizing gas in the disk from collapsing (i.e., so-called "morphological quenching"; Martig et al 2009).…”
Section: Structure Transformation and Quenchingmentioning
confidence: 99%
“…Galaxies appear to assemble their stellar mass mainly in two distinct modes: the "inside-out" and the "outside-in" mode (Pan et al 2016;Pérez et al 2013;Ibarra-Medel et al 2016;Goddard et al 2017). In the inside-out assembly mode, star formation cessation occurs first in galactic center with respect to the outskirts, which may be due to active galactic nucleus feedback (e.g.…”
Section: Introductionmentioning
confidence: 99%